Differences in cytotoxicity between 5% tetracycline hydrochloride and 15% EDTA as root canal irrigant - Devi Eka Juniarti; Karlina Samadi; Achmad Sudirman (Dental Journal (Majalah Kedokteran Gigi), 2008)
5% tetracycline hydrochloride and 15% EDTA as a root canal irrigant have been proven to be able to remove smear layer, open dentinal tubules and have antimicrobial activity. An effective root canal irrigation solution must be able to dissolve organic and anorganic debris, lubricate endodontic instruments, disinfect microorganism and non toxic. The purpose of this laboratory experimental study was to determine cytotoxicity differences between 5% tetracycline hydrochloride and 15% EDTA. 21 samples were used and classified into 3 groups: control, 5% tetracycline hydrochloride and 15% EDTA groups. Cytotoxicity test was done using BHK21 cells. The data was analyzed using Bird and Forrester formula. It concluded that 5% tetracycline hydrochloride more toxic than 15% EDTA as a root canal irrigant.